Applications of aspiration lung biopsy with special reference to the pathogenesis of the resolution of acute and chronic lobar pneumonia - Woolf, Colin Rael (Department of Clinical Laboratory Sciences, 2020)
Lung biopsy is neither widely known nor practiced and it was only in 1949 that i first came across a paper on this subject. The title was: "Cellular analysis of the aspiration lung biopsy from normal and some pathological conditions by Z. Godlowski" (1949). The very term "lung biopsy" conjures up the picture of a needle being introduced into an air filled, very vascular structure where the bleeding of an injured vessel cannot readily be stopped, where the stage is set for air embolisms and where tension pneumothorax may occur. it was with great surprise but also an apparently innocuous procedure. Unfortunately, at that time, there was no opportunity to use the method. In 1950 I became the University Assistant at the New Somerset Hospital in Cape Town. Many of the cases admitted to the wards presented with chest pathology. Patients with pneumococcal lobar pneumonia were not infrequent and occasional cases did not resolve as expected but went on to become so-called chronic pneumonia. What happened when an acute lobar pneumonia went on to the chronic stage and why did this occur? it was suggested that investigae this problem.